Peran E-Trust dalam Memediasi Pengaruh Social Media Marketing, E-WOM, dan Brand Image terhadap Purchase Intention Produk Fashion Jimshoney - Ekta Ratri Pramudita; Tri Septin Muji Rahayu (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
The rapid growth of the online fashion industry intensifies competition among local brands in the women's bags and wallets category. In regional markets like Purwokerto, consumers often face challenges regarding product quality doubts and digital transaction security. Therefore, this study aims to explore the effect of Social Media Marketing, Electronic Word of Mouth (e-WOM), and Brand Image on Purchase Intention, mediated by E-Trust, using the Stimulus-Organism-Response (SOR) framework. A quantitative approach was employed using online questionnaires distributed to 155 respondents in Purwokerto. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) assisted by SmartPLS. The results reveal that Social Media Marketing, e-WOM, and Brand Image positively and significantly impact Purchase Intention. Furthermore, E-Trust successfully mediates the relationship between these three marketing variables and the purchase intention for Jims Honey products. In conclusion, building consumer trust through effective digital marketing and a strong brand image is crucial for local businesses to boost online purchase intentions. These findings provide practical insights for fashion brands to optimize their digital presence and minimize consumer perceived risks.